Verbal literacy in the design process: Enthusiasm and reservation - Jara, Cynthia (ARCC Conference Repository, 2014)
This paper inquires into the role of verbal literacy in design processes and the teaching of design. During the Renaissance, Alberti identified literacy as the point of distinction separating an architect from a builder or crafts person. From the Renaissance through the nineteenth century, the idea of the architect as a liberally educated professional prevailed until Modernism in the twentieth century developed as an avant-garde movement, consciously seeking to negate the past. Experimental methods of teaching at the Bauhaus school in Germany emphasized visual thinking and encouraged disdain for traditional academic practices and values. Instructors from the Bauhaus eventually brought these ideas to the United States where they became firmly rooted during the post-World War II era. Gradually from the 1950s onward, Bauhaus methods were in turn perceived as stagnant, precipitating a search for new theories. Heuristic methodologies became a popular focus in the effort to re-establish design as a rigorous academic discipline. Around the same time or shortly afterward, an interest developed in the relevance of phenomenology to design, along with associated hermeneutic approaches. Heuristic and hermeneutic methods depend on verbal literacy, a shared requirement that should unite rather than divide them, but whether the two processes are complementary or opposed is far from clear. Critics of heuristic strategy disparage its techniques as reductive problem-solving, whereas hermeneutics is impugned for being arcane and cultish. Proponents of both sides can be found on most faculties of architecture, but may not be willing to speak to one another. The arguments of this paper rely on analysis to bring criticism into the open rather than assert a conclusion. My intention is to establish a common ground for discussion based on a better understanding of how design pedagogy relates to verbal literacy.